Influence of Low Order Harmonic Phase Angles on Tripping Time of Overcurrent Relays - Masoum, Mohammad; Masoum, Ali; Masoum, A. (University of Calgary, 2008)
Experimental analyses are used to investigate the impact of low order harmonics on the operation and tripping times of overcurrent relays. Two analytical approaches based on relay characteristics provided by the manufacturer and simulations using PSCAD software package are used to estimate tripping times under non-sinusoidal operating conditions. Experiments were conducted such that the order, magnitude and phase angle of harmonics could be controlled by employing a computer-based single-phase harmonic source. Computed and measured tripping times are compared and suggestions on the application of overcurrent relays in harmonically polluted environments are provided.